On the past activity of Sgr A*. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Ponti, G.; Morris, M. R.; Clavel, M.; Terrier, R.; Goldwurm, A.; Soldi, S.; Sturm, R.; Haberl, F.; Nandra, K.
Abstract: Recent X-ray emission events in the Galactic center would be expected to generate an X-ray reflection response within the surrounding clouds of the central molecular zone, in the Galactic disk and even, if powerful enough, in clouds outside our Galaxy. We review here the current constraints on Sgr A*'s past activity obtained through this method, with particular emphasis on the strong evidence that has been gathered for multiple X-ray flashes during the past few hundred years.